Applications of Tert-Butyl-Phenolic Antioxidants in Consumer Products and Their Potential Toxicities in Humans - Ngoc M. H. Hoang; Kwangsik Park (Toxics, 2024)
Tert-butyl phenolic antioxidants (TBP-AOs) are employed to inhibit oxidation and function as stabilizers and protectants in a broad spectrum of consumer products, such as food packaging, adhesives, lubricants, plastics, and cosmetics. The extensive utilization of TBP-AOs results in human exposure through various pathways. Furthermore, some TBP-AOs have been identified as potential endocrine disruptors and may cause liver and lung damage, as well as allergic reactions. Considering their varied applications and potential toxicity, a detailed evaluation of their safety profiles is imperative. However, existing research is often segmented and tends to focus narrowly on specific compounds. Consequently, this review collates recent data on TBP-AOs regarding their production, exposure, and toxicity, incorporating different databases and prior studies, as well as predictions of toxicity using ADMET. Our review strives to offer a comprehensive overview of the characteristics and health effects of TBP-AOs to guide future research and inform policy decisions.